2019
DOI: 10.1111/vsu.13307
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral fragments of the pastern joint at the origin of the collateral ligament of the distal sesamoid bone: performance after arthroscopic removal (2000–2015)

Abstract: Objective To describe the presence of fragments in the dorsal proximal interphalangeal (PIP) joint and to report flat racing performance after surgical treatment. Study design Retrospective study. Sample population Thirty‐nine affected thoroughbred flat racehorses and 169 age‐ and sex‐matched maternal siblings. Methods Medical records from 2000 to 2015 were reviewed for thoroughbred horses that underwent arthroscopic removal of osteochondral fragments in the dorsal aspect of the PIP joint. The horses’ 2‐year‐o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…The etiology of osteochondral fragmentation is deemed by many to be multifactorial and can be of developmental and traumatic origin ( 19 , 20 ). Surgical findings have indicated that fragments located at the dorsomedial and dorsolateral aspect of the PIPJ are often avulsion fractures at the origin of the collateral ligament of the distal sesamoid (navicular) bone and it is suggested that a traumatic etiology is more likely when accompanied by an aggressive proliferative reaction even when bilaterally present ( 21 ). In the Australian Thoroughbreds included in this study there were two with dorsomedial OCF and both had moderate associated PIPJ modeling.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of osteochondral fragmentation is deemed by many to be multifactorial and can be of developmental and traumatic origin ( 19 , 20 ). Surgical findings have indicated that fragments located at the dorsomedial and dorsolateral aspect of the PIPJ are often avulsion fractures at the origin of the collateral ligament of the distal sesamoid (navicular) bone and it is suggested that a traumatic etiology is more likely when accompanied by an aggressive proliferative reaction even when bilaterally present ( 21 ). In the Australian Thoroughbreds included in this study there were two with dorsomedial OCF and both had moderate associated PIPJ modeling.…”
Section: Discussionmentioning
confidence: 99%